Pendampingan Pengomposan Dengan Menggunakan Cairan Effective Microorganism (EM4) Di Lingkungan Sekolah Dasar Daerah Perbatasan: Indonesia - Herry Sanoto; Yosua Damas Sadewo; Sabinus Beni; Yeremia Niaga Atlantika (CV. Multi Kreasi Media, 2022)
State Elementary School 09 Rangkang is in Bengkayang District, Bengkayang Regency, West Kalimantan Province. Bengkayang Regency is geographically directly adjacent to neighboring Sarawak-Malaysia. In managing waste originating from the school environment, Elementary School 09 Rangkang has a management strategy by composting organic waste. Organic waste management at Elementary School 09 Rangkang together with the team aims to provide enrichment to practices regarding organic waste processing with composting. The process of composting organic waste uses the help of an Effective Microorganism (EM4) activator with the aim of accelerating composting and increasing the nutrients from composting. In this service, the implementation method applied is by identifying problems, implementing, and evaluating service activities. The results of the evaluation of this service activity show that the processing of organic waste in the school environment is an innovation in utilizing the waste that is generated every day. In addition, through this program, Elementary School 09 Rangkang teachers can gain competence in processing organic waste in the school environment.